Accommodating satisficing behaviour in stated choice experiments. (20th July 2018) - Sandorf, Erlend Dancke; Campbell, Danny
Abstract: Accumulating evidence suggests that respondents in stated choice experiments use simplifying strategies. Such behaviour is a deviation from random utility theory and can lead to wrong inferences regarding preferences. This is a first attempt to systematically explore satisficing in stated choice experiments. We consider 944 satisficing rules and allow respondents to revise the rules adopted throughout the choice sequence. Only a minority of respondents used the same satisficing rule across the entire sequence. Allowing for updating reveals that the use of the heuristic changes over the choice sequence. Considering satisficing behaviour leads to improved model fits and different marginal willingness-to-pay estimates.